Deterministic, Hybrid and Statistical Vibro-Acoustic Models - a Methodology to Determine the VLS Payload Fairing Acoustic Behavior - Rogerio Pirk; Carlos d´Andrade Souto (Journal of Aerospace Technology and Management, 2015)
Finite element method (FEM) and boundary element method (BEM) are methods usually applied on lowfrequency coupled fluid-structure analysis. On the other hand, statistical energy analysis (SEA) is a technique applied on small wavelength bandwidth predictions. However, in the midfrequency, where deterministic calculations are costly and confidence intervals of SEA are not satisfied, hybrid FEM/SEA models can be used. This work presents a coupled vibro-acoustic analysis methodology of the Brazilian Satellite Launcher Vehicle payload fairing. FEM/FEM model accounts for the low-frequency internal responses. The high-frequency responses are computed by a SEA coupled elasto-acoustic model, and a hybrid FEM/SEA model calculates the payload fairing mid-frequency behavior.